Mexican e-smes of artisan textile export in times of virtual integration and digital economies - Arellano Grajales, Beatriz (Posgrados de la División de Ciencias Económica Administrativas, 2021)
Cross-border electronic commerce in the context of the digital economy and open regionalism makes it possible to facilitate the export of the products of mexican artisans. This can be acchieved through the incentive to entrepreneurship of artisanal e-SMEs, at the same time, which reactivates the economy of the artisans themselves. In the same sense, the research answers the following questions which is the country with the highest demand for artisan productr to export by region (TTP11, TLCUEM 2.0, T-MEC and AP). What is the share of electronic commerce and cultural GDP in national GDP? And what is the capital raising process and where to go request private and government support?